PELATIHAN TEKNIK DASAR PENULISAN BERITA PADA REMAJA DI RUMAH KREATIF WADAS KELIR (RKWK), KARANGKLESEM PURWOKERTO SELATAN - Gita Anggria Resticka; Erwita Nurdiyanto; Octaria Putri Nurharyani; Nila Mega Marahayu; Rafli Adi Nugroho (Merwinspy Publisher, 2025)
One of the important language skills is writing skills. This skill is important because by writing someone can express their ideas or feelings. Wadas Kelir Creative House (RKWK), Karangklesem, South Purwokerto, is a community organization that houses highly creative teenagers with various lessons that focus on literacy. One of the activity units at RKWK is the Wadas Kelir writing school unit. This activity was carried out using a group achievement theory approach which consists of member input, mediating variables, group output and outcome achievements. The output of news writing articles is by the news writing structure which consists of headline, dateline, lead, body. Then, the news has important characteristics which are news characteristics, including timeliness, impact, prominence, proximity, singularity, conflict or controversy. Furthermore, types of news can include hard news (straight news) and soft news types (feature, dept news, investigation news, and opinion new).